(untitled) (RevistAleph, 2013)
O texto, a partir de alguns relatos sobre a experiência do Grupo Aleph, resgata aspectos da gênese do conceito "instituinte" que hoje tece as elaborações presentes na RevistAleph e em outros espaços científicos da educação. Com base nas reflexões de Célia Linhares, identificamos uma multiplicidade de interpretações e de conexões teóricas nas quais as experiências e os projetos instituintes articulam-se em análises realizadas por pesquisadores de diversas universidades brasileiras, sob diferentes olhares e enfoques educacionais. Destacamos as conexões com as elaborações de Benjamin, Castoriadis e Barbier, dentre outras. Nosso objetivo é socializar uma experiência formativa singular na pesquisa educacional: a criação e a transformação de uma perspectiva que ultrapassa os modelos prontos e burocráticos, considerando a pluralidade e as singularidades como potência para se realizarem as leituras das propostas educacionais em um Brasil que busca se democratizar. Palavras-chave: Grupo Aleph; experiêncas instituintes; instituído; instituinte. Abstract: The article, on the basis of a number of reports on the experience of the Aleph Group, recovers aspects of the origin of the “instituting” conception which nowadays weaves the current elaborations in the RevistAleph (Aleph Journal) and in many other scientific education spaces. On the basis of Célia Linhares reflections, we have identify a plurality of theoretical interpretations and connections in which instituting experiences and projects are articulated in analyses carried out by researchers of various Brazilian universities, from different educational ways of seeing and approaches. We highlight the connections with elaborations by Benjamin, Castoriadis and Barbier, among others. Our aim is to socialize an unique formative experience in educational research: the creation and transformation of a perspective which goes beyond the ready-made and bureaucratic models, considering the plurality and singularities as potency to perform the readings of educational proposals in a Brazil seeking to democratize itself. Keywords: Aleph Group; instituting experiences; instituted dimension; instituting dimension.